The extraction of asystasia gangetica using ethyl lactate solvent - Nur Fatihah, Hanafi (2015)
This paper presents the study of the leaves of Asystasia Gangetica. The leaves of Asystasia Gangetica are found to have a number of advantages to produce essential oil which is important in medicine, cosmetic and others. Asystasia Gangetica is a straggling herb usually found among short grasses and along pathways. The objective of this research is to obtain the essential oil from Asystasia Gangetica plant by using maceration method. The solvent used in this study is ethyl lactate. Prior to that, the leaves of Asystasia Gangetica need to be dried first at temperature 70°C to 90°C using oven. After drying, separately, the leaves and stems are cut into pieces. The small pieces of fresh samples (200 g) are extracted using the maceration and rotary evaporator methods are used to obtain the essential oil. The obtained result showed that optimum time is 7 days. Longer time operation and smaller particles size proved that higher yield is obtained. The presence of these components in the essential oil from leaves of Asystasia Gangetica is studied well. The essential oil is analysed using Gas Chromatography-Mass Spectrometer (GCMS). The result by GCMS showed that the essential oil contains hexadeconoic acid, n-hexadecanoic acid, phytol and 9, 12, 15-octadecatrienoic acid.